2016
DOI: 10.7567/jjap.55.04ej08
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of electrical transport properties of La4BaCu5− xCoxO13+δ conducting oxide thin films

Abstract: We fabricated Co-doped La4BaCu5O13+δ (La4BaCu5− x Co x O13+δ) epitaxial thin films with various amount of Co-substitution on SrTiO3 single-crystal substrates by a pulsed laser deposition method, and measured the resistivity from 10 to 1000 K. The resistivity below 700 K became large with increasing amount of Co-substitution, and that above 700 K was independent of Co-substitution. These measurement results suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…As shown in Figure 3b, the LBCO films on the SrTiO 3 single crystal substrate were in single phase and of better crystallinity, and the peaks to specific crystal planes became distinct. For the lattice mismatching, without crystal rotation, the lattice misfit between the a-axis of LBCO (≈8.65 Å) and the length of a two-unit cell of SrTiO 3 (7.82 Å) would be 10.6%, but with 26.6 • rotation, lattice misfit became −1.1%, as discussed in a previous report [14]. However, there is no clear evidence of grain orientation, despite the lattice parameters of (121) for LBCO and (101) for SrTiO 3 being identical, which suggests that the grains of the deposited film were rather randomly oriented.…”
Section: Xrd and Surface Structure Of Lbco Films After The Thermal Annealingsupporting
confidence: 53%
See 2 more Smart Citations
“…As shown in Figure 3b, the LBCO films on the SrTiO 3 single crystal substrate were in single phase and of better crystallinity, and the peaks to specific crystal planes became distinct. For the lattice mismatching, without crystal rotation, the lattice misfit between the a-axis of LBCO (≈8.65 Å) and the length of a two-unit cell of SrTiO 3 (7.82 Å) would be 10.6%, but with 26.6 • rotation, lattice misfit became −1.1%, as discussed in a previous report [14]. However, there is no clear evidence of grain orientation, despite the lattice parameters of (121) for LBCO and (101) for SrTiO 3 being identical, which suggests that the grains of the deposited film were rather randomly oriented.…”
Section: Xrd and Surface Structure Of Lbco Films After The Thermal Annealingsupporting
confidence: 53%
“…As it is well known, high-T c superconductivity is realized in layered cuprates with two-dimensional CuO 2 planes. The superconductivity was also achieved in quasi-one dimensional cuprates with a Cu 2 O 3 ladder such as (Sr,Ca) 14 Cu 24 O 41 [1]. Michel et al have investigated a La 4 BaCu 5 O 13+δ system and found that these perovskite-related copper oxides are highly metallic in conduction with a resistivity of 1.5 mΩcm at 673 K [2], and Murayama et al have substituted Sr for Ba to demonstrate metallic conduction but no superconductivity [3].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation